Effect of Marketing Mix Performance and Service Quality To Patient Loyality and Institutional Image and Implication On Hospital Performance (Survey on Police Hospital (Bhayangkara) in Indonesia) - RUSDIANTO . (Fakultas Ekonomi dan Bisnis Universitas Padjadjaran, 2015)
A Research in the dissertation analysis model on the hospital’s performance through the marketing mix performance variable and the service quality that supported by patient loyalty creation and institution imaging, where the hospital’s performance that became the object of research more or less not in line with the expectation, BOR, LOS, BTO and TOI are remain not optimum also the ROA itself still fluctuated. The study focused on the Police’s Hospital called Bhayangkara Hospital in entire Indonesia. Analysis unit in this research were the hospital and its patients also the management as the observation unit, whereas research method that being used are description and verification. The result of the test showing that marketing mix performance and the service quality were implemented properly, patients’ loyalty and imaging were made as it is even though the hospital’s performance are not fully okay. Mix marketing performance partially does not affect the patients’ loyalty and image whereas service quality partially does not affect the hospital’s performance but simultaneous marketing mix quality and the service quality quite influencing the patients’ loyalty, image and hospital’s performance. Marketing mix performance and the service quality directly or indirectly influencing the: patient loyalty through imaging, imaging through patients’ loyalty, and hospital’s performance through patient loyalty and imaging. Through a new model in this research the hospital’s performance could be built through patients loyalty improvement and imaging that being supported by improving the marketing mix performance and service quality.Keyword: Marketing mix performance , Service quality, Patients loyalty, Imaging, Hospital’s performance